Small Farm Mechanization Technologies and Transfer Strategies - Reddy, B. Sanjeeva; Srinivas, Indravarapu; Adake, Ravikanth V.; Thyagraj, C. R.; Reddy, K. Sammi; Rao, C. Srinivas (Indian Farming, 2016)
Â Â Â